Validity and Usability of Adjustment Worksheets for Computing Notebook Computer and Workstation Adjustments - Nanthavanij, Suebsak; Udomratana, Chatkate; Hansawad, Saowalak; Thepkanjana, Jayaporn; Tantasuwan, Wanchalerm (Science & Technology Asia, 2015)
The adjustment worksheets for computing notebook computer (NBC) and workstation adjustments is a successor of PostureAdjuster, a computerized tool for recommending necessary adjustments to help NBC users to sit with an appropriate seated posture during NBC operation. The adjustment worksheets contain tables and flow charts that enable NBC users to compute recommended adjustments based on the user’s gender, body (stature) height, NBC size, work surface height, and seat height. In this paper, the validity and usability of the adjustment worksheets are analytically and experimentally investigated. The results show that the adjustment worksheets are as effective as PostureAdjuster in providing valid recommendations for the NBC and workstation adjustments. Due to its simple layout design and step-by-step computation procedure, NBC users can learn to use the adjustment worksheets to compute the NBC and workstation adjustments easily and quickly. Keywords: Notebook computer, seated posture, usability, validity, office ergonomics